2010
DOI: 10.1175/2010jamc2245.1
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Blowing Snow and Precipitation on Snow Depth Change across the Ross Ice Shelf and Ross Sea Regions of Antarctica

Abstract: Measuring snowfall in the polar regions is an issue met with many complications. Across the Antarctic, ground-based precipitation measurements are only available from a sparse network of manned stations or field studies. Measurements from satellites promise to fill in gaps in time and space but are still in the early stages of development and require surface measurements for proper validation. Currently, measurements of accumulation from automated reporting stations are the only available means of tracking sno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(62 citation statements)
references
References 27 publications
1
61
0
Order By: Relevance
“…Lawson et al (2006) reported that at the South Pole Station blowing snow is observed when the wind speed exceeds about 4 m s −1 . Knuth et al (2010) measured a threshold of between 6.6 to 7.5 m s −1 at 10 m height for blowing dry snow at the Ross Ice Shelf. The threshold for blowing wet snow was higher at 8.5 to 9.6 m s −1 .…”
Section: Measurements Of Freezing Nuclei From the Balloonmentioning
confidence: 99%
“…Lawson et al (2006) reported that at the South Pole Station blowing snow is observed when the wind speed exceeds about 4 m s −1 . Knuth et al (2010) measured a threshold of between 6.6 to 7.5 m s −1 at 10 m height for blowing dry snow at the Ross Ice Shelf. The threshold for blowing wet snow was higher at 8.5 to 9.6 m s −1 .…”
Section: Measurements Of Freezing Nuclei From the Balloonmentioning
confidence: 99%
“…Figure 1 shows the climatological near-surface (850 hPa) winds on the Ross Ice Shelf (from the ERA-Interim reanalysis data), which illustrates the varying wind conditions experienced at different stations. Most of the AWS are located in katabatic outflow paths (Mary, Linda, Elaine, Ferrell, Nascent, and Byrd) and barrier wind regimes (Sabrina), and as a result these sites experience strong winds more often than the other sites (Braaten, 1997;Parish et al, 2006;Knuth et al, 2010;Nigro et al, 2011). We expect the snow accumulation at these sites may be more affected by wind redistribution than other sites such as Margaret, which is located on the eastern side of the RIS near Roosevelt Island.…”
Section: Site Description and Snow Accumulation Datamentioning
confidence: 97%
“…5, events that are in the region above the freshly fallen snow densities could have several causes: snow accumulation being limited by wind, higher snow densities due to wind-blown snow, or reanalysis overestimating event sizes; events that fall below the range could be either due to excess accumulation due to wind or reanalysis underestimating event sizes. At sites known to exhibit significant ablation such as Ferrell, Mary, Nascent, and Sabrina (Braaten, 1997;Knuth et al, 2010;Nigro et al, 2011), where we would expect a low bias in the ADG data (i.e. ADG snow accumulation is often limited due to wind), these sites do show a significant number of events where reanalyses are much larger than ADG events (except for the NCEP events with Mary).…”
Section: Reanalyses Datamentioning
confidence: 97%
See 2 more Smart Citations